2005
DOI: 10.1373/clinchem.2004.042093
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative DNA Damage, as Assessed by Urinary 8-Hydroxy-2′-Deoxyguanosine Concentrations, and Serum Redox Status in Persons Exposed to Mercury

Abstract: Background: Mercury is a ubiquitous and highly toxic environmental pollutant. In this study, we evaluated the relationship between mercury exposure and oxidative stress, serum and urinary mercury concentrations, oxidative DNA damage, and serum redox status in chronically mercury-exposed persons compared with healthy controls. Methods: We measured urinary 8-hydroxy-2-deoxyguanosine (8-OHdG), which we used as a biomarker of oxidative DNA damage in the mercury-exposed persons, by HPLC with electrochemical detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 36 publications
4
61
0
4
Order By: Relevance
“…It has been shown that 8-hydroxy-2'-deoxyguanosine (8-OHdG), a biomarker of oxidative DNA damage, is significantly elevated in urine samples of people from mercury-contaminated areas. 109 The concentrations of glutathione (GSH) and total protein thiols and the activities of glutathione peroxidase and superoxide dismutase were higher in the mercury-exposed group than in the control group. 84,109 Our recent study has also shown that mercury is capable of affecting the islet β-cell function and survival through an oxidative stress pathway in vivo and in vitro.…”
Section: Mercurymentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that 8-hydroxy-2'-deoxyguanosine (8-OHdG), a biomarker of oxidative DNA damage, is significantly elevated in urine samples of people from mercury-contaminated areas. 109 The concentrations of glutathione (GSH) and total protein thiols and the activities of glutathione peroxidase and superoxide dismutase were higher in the mercury-exposed group than in the control group. 84,109 Our recent study has also shown that mercury is capable of affecting the islet β-cell function and survival through an oxidative stress pathway in vivo and in vitro.…”
Section: Mercurymentioning
confidence: 98%
“…109 The concentrations of glutathione (GSH) and total protein thiols and the activities of glutathione peroxidase and superoxide dismutase were higher in the mercury-exposed group than in the control group. 84,109 Our recent study has also shown that mercury is capable of affecting the islet β-cell function and survival through an oxidative stress pathway in vivo and in vitro. 104,110 Low-dose mercury induced mouse pancreatic islet β-cell dysfunction through a PI3K-activated or oxidative stress-triggered Akt pathway in cell culture and animal models.…”
Section: Mercurymentioning
confidence: 98%
“…However, in unexposed populations taken as controls, blood mercury concentration was reported to be 2.73 ng/ mL in New York City adults and 1 ng/mL in China (14,15). For many years mercury was used in diuretics or as an ingredient of antiseptics (4).…”
Section: Mercurymentioning
confidence: 99%
“…Another important mechanism of exposure is fish consumption. Mercury attains 5.65 ng/mL among regular fish consumers (13,14) and levels of 7 to 10 ng/mL among exposed workers (10,15).…”
Section: Mercurymentioning
confidence: 99%
“…Posteriormente, foi investigado o possível efeito modulador dos micronutrientes também provenientes da dieta alimentar e das características sociais e demográficas sob os biomarcadores de estresse oxidativo e Hg-S. , 1998;BULAT et al, 1998;CHEN et al, 2005;GROTTO et al, 2010GROTTO et al, , 2011aHUSSAIN et al, 1999;PINHEIRO et al, 2008). (DA SILVA et al, 2007;PEROTTONI et al, 2004;VALENTINI et al, 2007VALENTINI et al, , 2008VALENTINI et al, , 2009.…”
Section: Discussionunclassified